PARTNER, CoreValve, and CHOICE: A Review of 3 State-of-the-Art TAVR Trials - Vinall, Maria (MD Conference Express, 2014)
This article provides a broad overview of the methodology, major findings, and impact of the 3 major transcatheter aortic valve replacement (TAVR) trials (PARTNER, CoreValve, and CHOICE) along with some perspective.